Clima social en la familia y su relación con la inteligencia emocional de los estudiantes del 6to grado de primaria de la I.E N°00536 Manuel Segundo del Águila - Villanueva Díaz, Deysi Miriam (2011)
The present experimental work was realized to determine the relation of the social climate in the family with the emotional intelligence of the students of the sixth degree of Primary Education of the Educational lnstitution N ° 00536 11 Manuel Segundo of the Eagle Velazques 11 of the district of Rioja in the year 201 O. The investigation of substantive, of the descriptiva level, of design transaccional correlaciona!, was developed by a sample of 138 students, who developed the scale of social climate in the family and the inventory of emotional intelligence. The gathered information was processed by means of the distribution of frequencies and the coefficient of Pearson's correlation, for the test of hypothesis, the coefftcient of Perason's correlation, Student was processed and analyzed by means of her t. The results confirm the hypothesis of investigation, the social climate in the family relates significantly to the emotional intelligence of the students of the sixth degree of Primary Education of the Educational lnstitution N o 00536 11 Manuel Segundo of the Eagle Velazques " of the district of Rioja in the year 201 O, obtaining, tc=6,05, major to t tabulated, tt=1 ,65, with 5 % of the leve! of significancia and n - 2 degrees of freedom.